Variations in peak nasal inspiratory flow among healthy students after using saline solutions - Olbrich Neto, Jaime [UNESP] (2015)
Nasal hygiene with saline solutions has been shown to relieve congestion, reduce the thickening of the mucus and keep nasal cavity clean and moist. Evaluating whether saline solutions improve nasal inspiratory flow among healthy children. Students between 8 and 11 years of age underwent 6 procedures with saline solutions at different concentrations. The peak nasal inspiratory flow was measured before and 30min after each procedure. Statistical analysis was performed by means of t test, analysis of variance, and Tukey's test, considering p<0.05. We evaluated 124 children at all stages. There were differences on the way a same concentration was used. There was no difference between 0.9% saline solution and 3% saline solution by using a syringe. The 3% saline solution had higher averages of peak nasal inspiratory flow, but it was not significantly higher than the 0.9% saline solution. It is important to offer various options to patients.